Пошаговое объяснение:
1) 4a^2+12ab+9b^2
2) 4a^2-12ab+9b^2
3) 16a^2-49
4) a^4-b^6
5) 36x^2-1292
1)4a^2+12ab+9b^2 (a+b)^2=a^2+2ab+b^2
2)4a^2-12ab+9b^2 (a-b)^2=a^2-2ab+b^2
3)16a^2-49 (a+b)(a-b)=a^2-b^2
4)a^4-b^9 (a+b)(a-b)=a^2-b^2
5)4(9(x^2-9)+1) (a-1)(a+1)=a^2-1
Пошаговое объяснение:
1) 4a^2+12ab+9b^2
2) 4a^2-12ab+9b^2
3) 16a^2-49
4) a^4-b^6
5) 36x^2-1292
1)4a^2+12ab+9b^2 (a+b)^2=a^2+2ab+b^2
2)4a^2-12ab+9b^2 (a-b)^2=a^2-2ab+b^2
3)16a^2-49 (a+b)(a-b)=a^2-b^2
4)a^4-b^9 (a+b)(a-b)=a^2-b^2
5)4(9(x^2-9)+1) (a-1)(a+1)=a^2-1